1979
DOI: 10.1002/1520-6629(197907)7:3<198::aid-jcop2290070303>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of interorganizational interaction in social service agencies

Abstract: The problem of interorganizational interaction was reviewed in terms of organizational structure and process, organizational size, and domain consensus between organizations. In order to determine the relationship between these factors and interorganizational interaction, interview data were gathered from personnel in a sample of 27 social service agencies. Cluster analysis results indicated a strong relationship between relationships of goal/task similarity and the degrees of interorganizational interaction r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…On the other hand, research has shown that commitment to clear and consensually agreed upon purposes or goals is important for partnerships (Boudreau, 1991;Butterfoss, Goodman, & Wandersman, 1993;Gray, 1989;Labonté, 1993;MacGillivary & Nelson, 1998;Panet-Raymond, 1992;Stewart, Banks, Crossman, & Poel, 1994;Tornatzky & Lounsbury, 1979). Gray (1989) calls the process of developing a shared mission "direction setting" and emphasizes the need for a superordinate goal that fits for all partners.…”
Section: Developing Shared Values For Value-based Partnershipsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, research has shown that commitment to clear and consensually agreed upon purposes or goals is important for partnerships (Boudreau, 1991;Butterfoss, Goodman, & Wandersman, 1993;Gray, 1989;Labonté, 1993;MacGillivary & Nelson, 1998;Panet-Raymond, 1992;Stewart, Banks, Crossman, & Poel, 1994;Tornatzky & Lounsbury, 1979). Gray (1989) calls the process of developing a shared mission "direction setting" and emphasizes the need for a superordinate goal that fits for all partners.…”
Section: Developing Shared Values For Value-based Partnershipsmentioning
confidence: 99%
“…Organizational-level partnership outcomes can include both a newly formed partnership organization (e.g., a coalition or consortium) and member organizations (including those operated exclusively operated by oppressed groups). The values of caring, compassion, community, and health suggest the need to examine outcomes such as social support and organizational climate (Pretty & McCarthy, 1991), morale of organizational members (Fineman, 1993), and cooperation between organizations operated by different stakeholders (Tornatzky & Lounsbury, 1979). In terms of stakeholder participation, self-determination, and power sharing, several researchers have identified the qualities of empowering organizational contexts, including a belief system that inspires growth and focuses on strengths, opportunities for member participation and contribution, social support, shared leadership, and organizational power to effect community change (e.g., Maton & Salem, 1995;Segal, Silverman, & Temkin, 1995).…”
Section: Organizational-level Outcomesmentioning
confidence: 99%